Gap Junction Intercellular Communication Negatively Regulates Cadmium-Induced Autophagy and Inhibition of Autophagic Flux in Buffalo Rat Liver 3A Cells - Zou, Hui; Yuan, Junzhao; Zhang, Yi; Wang, Tao; Chen, Yan; Yuan, Yan; Bian, Jianchun; Liu, Zongping (Frontiers in Pharmacology, 2020)
Cadmium is an important environmental pollutant that poses a serious threat to the health of humans and animals. A large number of studies have shown that the liver is one of the important target organs of cadmium. Stimulation of cells can lead to rapid changes in gap junction intercellular communication (GJIC) and autophagy. Previous studies have shown that cadmium can inhibit GJIC and induce autophagy. In order to understand the dynamic changes of GJIC and autophagy in the process of cadmium-induced hepatotoxic injury and the effects of GJIC on autophagy, a time-gradient model of cadmium cytotoxicity was established. The results showed that within 24 h of cadmium exposure, 5 μmol/L cadmium inhibited GJIC by down regulating the expression levels of connexin 43 (Cx43) and disturbing the localization of Cx43 in Buffalo rat liver 3A (BRL 3A) cells. In addition, cadmium induced autophagy and then inhibited autophagic flux in the later stage. During this process, inhibiting of GJIC could exacerbate the cytotoxic damage of cadmium and induce autophagy, but further blocked autophagic flux, promoting GJIC in order to obtain the opposite results.